Hieracia balcanica XVII. Hieracium wierzbickii (Asteraceae) a new hybridogenous species from Banat in Romania - Szeląg, Zbigniew (Phytotaxa, 2019)
Hieracium wierzbickii, a new, apomictic, triploid (x = 9) species of presumably hybrid origin between sexual, diploid H. umbellatum and agamospermous, tetraploid H. wiesbaurianum subsp. herculanum, is described from Banat in Southern Romania, and illustrated by a photograph of the holotype. This is the first Hieracium species of the morphological formula H. umbellatum – H. wiesbaurianum.